2014
DOI: 10.1007/978-3-319-13647-9_20
|View full text |Cite
|
Sign up to set email alerts
|

Restaurant Information Extraction (Including Opinion Mining Elements) for the Recommendation System

Abstract: Abstract. In this paper information extraction method for the restaurant recommendation system is proposed. We aim at the development of an information extraction (IE) system which is intended to be a module of the recommendation system. The IE system is to gather information about different aspects of restaurants from online reviews, structure it and feed the recommendation module with the obtained data. The analyzed frames include service and food quality, cuisine, price level, noise level, etc. In this pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…It should be also stated that including emoticons and exclamations into the feature set is not a good idea unless the aspect is service quality. For the other aspects it does not improve F1 or even impairs it [28].…”
Section: A Restaurant Information Extractionmentioning
confidence: 87%
See 3 more Smart Citations
“…It should be also stated that including emoticons and exclamations into the feature set is not a good idea unless the aspect is service quality. For the other aspects it does not improve F1 or even impairs it [28].…”
Section: A Restaurant Information Extractionmentioning
confidence: 87%
“…The predicative-attributive dictionaries were chosen, in particular for adjectives and full and short participles, which refer to nominations of the key frames. This is conditioned by the POS distribution analysis within corpus n-grams showed dominating of noun phrases in most aspects description [28].…”
Section: B Museums Information Extractionmentioning
confidence: 96%
See 2 more Smart Citations
“…They showed that their model achieved an accuracy almost like offline methods. Ekaterina Pronoza [6] et.al projected a eating house info extraction technique for the eating house recommendation system. Veda Waikul [7] et.al projected an SVM classifier for classifying restaurant reviews.…”
Section: Literature Reviewmentioning
confidence: 99%